2018
DOI: 10.5395/rde.2018.43.e1
|View full text |Cite
|
Sign up to set email alerts
|

Root canal irrigants influence the hydrophobicity and adherence of Staphylococcus epidermidis to root canal dentin: an in vitro study

Abstract: ObjectivesTo determine the effect of root canal irrigants on the hydrophobicity and adherence of Staphylococcus epidermidis (S. epidermidis) to root canal dentin in vitro.Materials and MethodsRoot dentin blocks (n = 60) were randomly divided into 4 groups based on the irrigation regimen: group 1, saline; group 2, 5.25% sodium hypochlorite (NaOCl); group 3, 5.25% NaOCl followed by 17% ethylenediaminetetraacetic acid (EDTA); group 4, same as group 3 followed by 2% chlorhexidine (CHX). The hydrophobicity of S. ep… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
2
0
2

Year Published

2021
2021
2023
2023

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 40 publications
(46 reference statements)
0
2
0
2
Order By: Relevance
“…The microbial adhesion to solid surface is the first step for biofilm formation [ 63 ]. Studies showed that chemical agents have the ability to change the physicochemical properties of dentine which can influence the nature of adherence of microorganism to dentine [ 37 , 64 ]. Hence investigating the influence of 2%K21 on the adherence of E. faecalis and C. albicans to root canal dentine would be of importance.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The microbial adhesion to solid surface is the first step for biofilm formation [ 63 ]. Studies showed that chemical agents have the ability to change the physicochemical properties of dentine which can influence the nature of adherence of microorganism to dentine [ 37 , 64 ]. Hence investigating the influence of 2%K21 on the adherence of E. faecalis and C. albicans to root canal dentine would be of importance.…”
Section: Discussionmentioning
confidence: 99%
“…Dentin blocks were stained and counterstained with acridine orange (AO) (Sigma-Aldrich, St. Louis, MO, USA) and 0.1% crystal violet (Sigma, St. Louis, MO, USA) for 15 and 5 min respectively. The blocks were observed under fluorescent microscope (Eclipse TiU, Nikon, Tokyo, Japan) [ 37 , 38 ]. An independent blinded observer examined five different dentin blocks at three randomly selected areas.…”
Section: Methodsmentioning
confidence: 99%
“…As características ideais para um bom irrigante são: a destruição arquitetura do biofilme; a lubrificação do canal radicular; a desinfecção eficaz; a biocompatibilidade com o complexo dentino-pulpar; o efeito antibacteriano e descalcificante. Entretanto, as soluções atualmente comercializadas não atendem a todos estes requisitos simultaneamente 5 .…”
Section: Introductionunclassified
“…As soluções irrigantes mais utilizadas no estágio de limpeza química no tratamento do canal radicular são hipoclorito de sódio (NaOCl), ácido etilenodiaminotetracético (EDTA) e clorexidina (CHX). As soluções nanoparticuladas de prata e de óxido de zinco, juntamente com os irrigantes a base de vegetais, têm ganhado o foco como alternativas aos irrigantes convencionais, sendo desenvolvidos estudos com o intuito comprovar a eficiência destes [4][5][6] .…”
Section: Introductionunclassified